Addisonian Crisis Precipitated By Thyroxine Therapy In A Patient With Type 2 Autoimmune Polyglandular Syndrome - Pokharel, Sunil; Shrestha, A; Maksey, D; Shrestha, B; Paudel, P; Shrestha, B; Dhital, BM (Journal of Chitwan Medical College, 2014)
Primary hypoadrenalism(Addison’s disease) refers to glucocorticoid deficiency occurring in the setting of adrenal disease(mostly due to autoimmune adrenalitis), whereas secondary hypoadrenalism arises because of deficiency of ACTH(mostly due to pituitary disease) . A major distinction between these two is that mineralocorticoid deficiency invariably accompanies primary hypoadrenalism, but this does not occur in secondary hypoadrenalism because only ACTH is deficient; the renin-angiotensin-aldosterone axis is intact and in primary hypoadrenalism skin pigmentation is always present due to increased ACTH secretion(unless of short duration) but it is absent in secondary hypoadrenalism. Addison’s disease or primary adrenocortical failure was first described by English physician Thomas Addison, who found it in six patients with adrenal tuberculosis in 1855(1). Addisonian crisis is a potentially fatal condition associated mainly with an acute deficiency of the glucocorticoid cortisol and, to a lesser extent, the mineralocorticoid aldosterone. This is a rare condition with an estimated incidence in the developed world of 0.8 cases per 100,000 and prevalence of 4 to 11 cases/100,000 population. Despite optimised life-saving glucocorticoid replacement and mineralocorticoid-replacement therapy, it is life threatening if overlooked(2-3). Hypothyroidism may mask the addison’s disease so in patients with panhypopituitarism and autoimmune polyglandular syndrome type 2 thyroxine replacement without adequate steroid replacement may precipitate acute addisonian crisis. Journal of Chitwan Medical College 2013; 3(4); 54-56 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9557